PERSEPSI MASYARAKAT SURABAYA TENTANG IKLAN â€œMANFAAT PAJAKâ€ DI TELEVISI - Ulfa, Anita; Darmawan, Arif; Soenarjanto, Bagus (representamen, 2015)
Perception is a stimulus that is perceived by the individual, organized and then interpreted so thatthe individual realizes and understands what is perceived. In other words perception is a process thatinvolves the entry of messages or information into the human box. Perception is called the core ofcommunication because if individual perceptions are inaccurate, then the individual is not likely tocommunicate effectively. Perceptions that determine the individual to choose a message and ignore theother message. The research with the title of perception of Surabaya society about advertisement of "taxbenefit" in television is a research which aims to know how perception of advertisement. This study useddescriptive qualitative. From the research conducted, perception is negative. This can be known fromsome interviews that were asked to informants, most informants stated disagree. But there's still a smallpercentage who have an unfavorable perception of "tax benefit" ads on television, because ads areconsidered to get support in the advertising process. Everything presented in the ad. From the results ofresearch that has been obtained then the advice given to advertisers "tax benefits" on television. Showingexaggerated imagery that is advertised because it can be a bad impression to the advertised.Keywords: perception, advertising, taxes, mass media